Efficiency of zeolite as urea additive and mycorrhizal inoculation on wheat crop - Osuna-Ceja, Esteban Salvador; María-Ramírez Andrés; Paredes-Melesio, Roberto; Padilla Ramírez José Saúl; Báez-González Alma Delia (Revista Mexicana de Ciencias Agrícolas, 2018)
Zeolite and mycorrhizae are natural products that are useful in agriculture. The former retains ammonium in both its internal and external structure, acting as a reservoir of slowly released nitrogen fertilizer, while the latter is a complex of soil fungi that form mutualistic symbiosis with the roots of plants and increase the absorption of phosphorus to the plant. This study aims to evaluate the efficiency of the use of urea combined with zeolite and mycorrhizae on wheat crop under irrigation. The study was conducted in Pabellón, Aguascalientes, Mexico, from December 2009 to May 2010. The following combinations of zeolite and urea were evaluated: 25% zeolite-75% urea, 0% zeolite-100% urea and 0% zeolite-0% urea with and without mycorrhizae, for a total of six treatments. The treatments were established on strips (16.67m x 100m) of 1 667m2 each. Seed yield, flag leaf (HB) N concentration at grain filling stage and some soil properties were evaluated. The results show that urea combined with 25% zeolite enabled the substitution of 25% of the nitrogen fertilization for the crop with or without mycorrhizae and significantly increased wheat yield.